Effective Interpersonal Communication Training for Healthcare Workers to Improve Patient Satisfaction in Health Care Facilities - Tiara Putri Ryandini; Nurhadi, Mokhamad; Widyawati, Mei; Tiara putri (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Interpersonal communication plays a critical role in determining patient satisfaction and the quality of healthcare services. However, many healthcare workers in primary care settings lack adequate training in communication skills, leading to misunderstandings, decreased patient trust, and suboptimal service experiences. This community service program was implemented through a two-day interactive training for 25 healthcare workers at a local health facility. The methods included pre- and post-assessments, lectures, case discussions, roleplays, and simulation practices. Evaluation was conducted through knowledge tests and participant feedback. The training resulted in a significant increase in participants' knowledge scores, from an average of 62.4% (pre-test) to 86.1% (post-test). Simulation activities showed improved communication techniques such as active listening and empathetic responses. Additionally, 96% of participants expressed high satisfaction with the training and a strong willingness to apply the skills in their clinical practice. The results highlight that structured, practical communication training can enhance healthcare workers' competencies and foster more patient-centered interactions. Continued implementation of similar programs and integration into institutional development plans are recommended to support long-term impact.